Description of medication errors detected at a drug information centre in Southern Brazil - dos Santos L; Winkler N; dos Santos MA; Martinbiancho JK (Centro de Investigaciones y Publicaciones Farmaceuticas, 2015)
Objective: To identify and describe actual or potential medication errors related to drug information inquiries made by staff members of a teaching hospital to a Drug Information Centre from January 2012 to December 2013. Methods: Data were collected from the records of inquiries made by health care professionals to the Drug Information Centre throughout this period. Results: During the study period, the Drug Information Centre received 3,500 inquiries. Of these, 114 inquiries had medication errors. Most errors were related to prescribing, preparation, and administration and were classified according to severity as category B (57%) (potential errors) and categories C (26.3%) and D (15.8%) (actual errors that did not result in harm to the patient). Error causes included overdose (13.2%), wrong route of administration (11.4%), inadequate drug storage (11.4%), and wrong dosage form (8.8%). The drugs most frequently involved in errors were vitamin K (4.4%), vancomycin (3.5%), and meropenem (3.5%). Conclusion: In this study, it was not possible to measure the reduction in error rate involving medication use because of the lack of previous data on this process in the institution. However, our findings indicate that the Drug Information Centre may be used as a strategy to seek improvements in processes involving medication use.